Literary-linguistic norm in the dictionary of the serbian language (single volume) and teaching practice - Goran N. Zeljić; Ljubica D. Vesić (University of Belgrade, Teacher Education Faculty, 2024)
The paper examines the place of the Dictionary of the Serbian Language (Matica srpska, 2007/2011/2018) among the normative manuals that support Serbian literary and linguistic norm. In addition to orthography manuals (Pravopis srpskog jezika, Matica srpska, 2010) and grammar (Normativna gramatika, Piper et al.), it considers descriptive monolingual dictionaries of the literary/standard language, such as the six-volume dictionary MS/MH (1967-1976), and the one-volume Dictionary of the Serbian Language (MS, 2007/2011/2018). For the purposes of the paper, several dictionary determinants/lemmas were selected in the dictionary article which include grammemes and grammatical characteristics that are part of the literary-linguistic norm, namely gender, number, morphological and morphonological forms, etc. The aim of the research was to determine which grammatical features are highlighted in the Dictionary of the Serbian Language and whether they are aligned with the grammar and orthography norms, and how these features can be pointed out in the teaching of the Serbian language at the school and university level.